Evaluation of confirmatory data following the Article 12 MRL review for thiabendazole. (25th August 2022) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Cabrera, Luis Carrasco; Castellan, Irene; Ferreira, Lucien; Giner, German; Greco, Luna; Jarrah, Samira; Leuschner, Renata; Magrans, Jose Oriol; et al.
Abstract: The applicant Syngenta Crop Protection AG submitted a request to the competent national authority in Spain to evaluate the confirmatory data that were identified for in the framework of the maximum residue level (MRL) review under Article 12 of Regulation (EC) No 396/2005 as not available. To address the data gaps, a new storage stability study, new residues trials and a validated analytical enforcement method for the determination of the relevant residues in animal products were submitted. The data gaps were considered satisfactorily addressed for the plant commodities. The new information provided required a revision of the existing MRL for avocados. As regards the commodities of animal origin, the data gaps were only partially addressed and therefore further risk management considerations are required regarding the revision of the existing MRLs which were derived from Codex MRLs. The risk assessment performed for thiabendazole was also updated. No risk was identified.